2001
DOI: 10.1177/002221940103400202
|View full text |Cite
|
Sign up to set email alerts
|

Role of Visual Attention in Cognitive Control of Oculomotor Readiness in Students with Reading Disabilities

Abstract: This study investigated eye movement and comprehension therapy in Grade 6 children with reading disabilities (RD). Both order of therapy and type of therapy were examined. Furthermore, the implications of visual attention in ameliorating reading disability are discussed. Thirty-one students with RD were identified using standardized reading comprehension tests. Eye movements were analyzed objectively using an infra-red recording device. Reading scores of participating children were 0.5 to 1 SD below the nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
4
27
0
1
Order By: Relevance
“…First, the OVR-related aspects were directly trained and not the visual/general attentional aspects per se. Second, the findings of Solan et al [33,59] would be consistent with this conclusion. In children with oculomotor-based reading problems, they performed either oculomotor, cognitive (comprehension) or attentional training in three matched groups.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…First, the OVR-related aspects were directly trained and not the visual/general attentional aspects per se. Second, the findings of Solan et al [33,59] would be consistent with this conclusion. In children with oculomotor-based reading problems, they performed either oculomotor, cognitive (comprehension) or attentional training in three matched groups.…”
Section: Discussionsupporting
confidence: 62%
“…They found that all three types of training improved reading ability, but with the attentional training showing considerably lower gains than for either the oculomotor or cognitive ones. Such a study incorporating the test vehicles of the Solan et al [33,59] group should be performed to tease out more directly this important question in the mTBI population.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators hypothesize that a lack of synchronization in timing between magnocellular and parvocellular activations in dyslexics may prevent effective sequential processing, pattern analysis, and figure-ground discrimination, and hence impede development of efficient reading and attention skills (Stein and Walsh, 1997; Vidyasagar, 1999, 2012, 2013; Lawton, 2000, 2007, 2008, 2015, 2016; Stein, 2001). It is further possible that the dyslexic reader’s deficit in attentional focus (Vidyasagar, 1999, 2012; Solan et al, 2001; Valdois et al, 2004; Facoetti et al, 2006; Lawton, 2016) is another consequence of sluggish magnocellular neurons, preventing the linked parvocellular neurons from isolating and sequentially processing the relevant information needed for reading (Vidyasagar, 1999), and not from the information overload as proposed previously (Stuart et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Eye-movement recording data show a reader's difference in visual performance when reading orally and silently (Solan, Larson, Shelley-Tremblay, Ficarra, & Silverman, 2001). Reports of some students' performances in both oral reading and silent reading, show a loss of binocular coordination and accuracy in visual tracking when they read aloud as contrasted with their visual performance when reading silently.…”
Section: Visual/functional Performance Examinationmentioning
confidence: 95%